PERAN DINAS PEMBERDAYAAN PEREMPUAN DALAM MENGATASI KEKERASAN RUMAH TANGGA DI KOTA BATAM - Nurjannah, Nurjannah; Putra, Bobby Mandala (SCIENTIA JOURNAL, 2019)
Domestic violence is one of the Nasional problem. This is indicated by Law No. 23 of 2004 about elimanation of domestic violence. In 2017 there were 300.000 cases and 259.150 were cases of women. In the city of Batam institution to hat handles cases of domestic violence is the service of empowering women and children (PPPA). In the last 3 years is increased especially women. The PPPA city office in Batam overcomes cases of domestic violence in 2016 dealing with 15 victims, in 2017 21 victims and in 2018 as many as 34 victims. This is one reason researchers conduct research. This research was carried out to the extent of the PPPA service in handling cases of domestic violence. The method used is descriptive qualitative. Data collection techniques are carried out through observation, interview and observation. The results of the study were: the role of PPPA Batam in handling cases of domestic violence, the obstacles and solution needed by the PPPA service Batam City in overcoming the problem of dome. This research is expected to contribute knowledge in handling the problem of domestic violence and is used as a consideration for policy actors to solve the problem of domestic violence.